Transitional justice in Africa : policy implications of the African Union Transitional Justice Policy (AUTJP) for women and youth on the continent - Matshaka, Chenai (University of Pretoria, 2023)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2022.